Anoxygenic photo- and chemo-synthesis of phototrophic sulfur bacteria from an alpine meromictic lake. Issue 3 (29th January 2021) - Di Nezio, Francesco; Beney, Clarisse; Roman, Samuele; Danza, Francesco; Buetti-Dinh, Antoine; Tonolla, Mauro; Storelli, Nicola
ABSTRACT: Meromictic lakes are interesting ecosystems to study anaerobic microorganisms due their permanent stratification allowing the formation of a stable anoxic environment. The crenogenic meromictic Lake Cadagno harbors an important community of anoxygenic phototrophic sulfur bacteria responsible for almost half of its total productivity. Besides their ability to fix CO2 through photosynthesis, these microorganisms also showed high rates of dark carbon fixation via chemosyntesis. Here, we grew in pure cultures three populations of anoxygenic phototrophic sulfur bacteria previously isolated from the lake, accounting for 72.8% of the total microbial community and exibiting different phenotypes: (1) the motile, large-celled purple sulfur bacterium (PSB) Chromatium okenii, (2) the small-celled PSB Thiodictyon syntrophicum and (3) the green sulfur bacterium (GSB) Chlorobium phaeobacteroides . We measured their ability to fix CO2 through photo- and chemo-synthesis, both in situ in the lake and in laboratory under different incubation conditions. We also evaluated the efficiency and velocity of H2 S photo-oxidation, an important reaction in the anoxygenic photosynthesis process. Our results confirm that phototrophic sulfur bacteria strongly fix CO2 in the presence of light and that oxygen increases chemosynthesis at night, in laboratory conditions. Moreover, substancial differences were displayed between the three selected populations in terms of activity and abundance. Abstract : The ecological role of three different species of anoxygenic phototrophic sulfur bacteria from the chemocline of an alpine meromictic lake was investigated through a combination of field and laboratory experiments.